2014
DOI: 10.4314/bcse.v28i3.2
|View full text |Cite
|
Sign up to set email alerts
|

Trace determination of bisphenol-A in landfill leachate samples by dispersive liquid- liquid microextraction followed by high performance liquid chromatography

Abstract: ABSTRACT. A simple, rapid and efficient sample pretreatment technique, termed dispersive liquid-liquid microextraction (DLLME), was developed as an extraction methodology to determine bisphenol-A (BPA), in landfill leachate samples prior to high performance liquid chromatography (HPLC)-ultraviolet detection. Some effective parameters, such as pH, extraction and disperser solvent type and their volumes, time of extraction and salt effect have been optimized using the one-factor-at-a-time approach. Under the opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…3 A Main purpose of the analyzed studies as revealed by the publications in Table S1. B Overlapped main purposes with other secondary objectives of the analyzed papers [64] or by air pollution near polycarbonate molding plants [65], bee pollen [66], mussels [67] and brine shrimp [68]. Food contamination was determined in meat samples [53], beverages [55,69,70], milk [59,63,71,72], oils [56,63], and canned food products [59,71,73] with most studies revealing that BPA could be leached from the plastic can linings, packaging, and bottles [53,55,56,71,[74][75][76].…”
Section: Temporal Distribution and Purpose Of The Selected Articlesmentioning
confidence: 99%
“…3 A Main purpose of the analyzed studies as revealed by the publications in Table S1. B Overlapped main purposes with other secondary objectives of the analyzed papers [64] or by air pollution near polycarbonate molding plants [65], bee pollen [66], mussels [67] and brine shrimp [68]. Food contamination was determined in meat samples [53], beverages [55,69,70], milk [59,63,71,72], oils [56,63], and canned food products [59,71,73] with most studies revealing that BPA could be leached from the plastic can linings, packaging, and bottles [53,55,56,71,[74][75][76].…”
Section: Temporal Distribution and Purpose Of The Selected Articlesmentioning
confidence: 99%
“…The solvent microextraction technique such as dispersive liquid-liquid microextraction (DLLME) [18][19][20][21][22][23] which overcomes these problems by reducing the amount of the organic solvent have been used to extract and determination of OPPs pesticides [24]. Extraction solvents often used in DLLME are chlorobenzene, carbon tetrachloride and chloroform with higher density than water and all of which are potentially toxic to human and the environment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, endocrine disturbing chemicals have been identified as the most notorious contaminants (Canale et al, 2010;Jing et al, 2011;Cai et al, 2004). Out of this, about 100 tons is released into the environment (Bahramifar et al, 2014;Rykowska and Wasiak, 2006). BPA is produced worldwide, with an estimated production of 3.9 million tons in 2006 (Ballesteros-Gómez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…BPA is produced worldwide, with an estimated production of 3.9 million tons in 2006 (Ballesteros-Gómez et al, 2009). Out of this, about 100 tons is released into the environment (Bahramifar et al, 2014;Rykowska and Wasiak, 2006). BPA is a typical product of the industrial society produced in large quantities worldwide, 90% or more being used as a monomer for the production of polycarbonate plastics (PC), epoxy resins used to line metal cans and in many plastic consumer products including toys, water pipes, drinking containers, eyeglass lenses, sports safety equipment, dental monomers, medical equipment and tubing, polysulfone, polyacrylate, polyetherimide, unsaturated polyester and phenolic (Asimakopoulos et al, 2012;Vandenberg et al, 2007).…”
Section: Introductionmentioning
confidence: 99%